Peranan Sektor Industri Pengolahan dalam Perekonomian Nusa Tenggara Timur - Koylal, Johny Agustinus; Kuang, Stefanus M.; Abineno, Jemseng C. (Jurnal Penelitian Pertanian Terapan, 2024)
The alignment of economic growth between the processing industry sector and the agricultural sector in the economy will encourage the transfer of surplus labor from the agricultural sector to the processing industry sector. Furthermore, these conditions will have an impact on marginal increases in labor productivity and income in the agricultural sector as well as demand for processing industry products. This study examines the structure of demand and supply, output, gross value added, and final demand of the processing industry sector in the economy of East Nusa Tenggara. The study was conducted from April to October 2023. The analysis method used is a quantitative analysis of the East Nusa Tenggara Input-Output Table in 2020 which was compiled from the update of the East Nusa Tenggara Input-Output Table in 2017. The results of the analysis show that based on the output and gross value added generated in the economy, the food and beverage industry sector can be categorized as a leading processing industry sector. The processing industry sector uses inputs that mostly come from production within the region and the final demand of the sector is mostly used for household consumption. Policymakers need to prioritize the development of the leading processing industry sector, namely the food and beverage industry sector based on domestic inputs, especially inputs originating from the agricultural sector to increase competitiveness and be able to meet intermediate demand by other economic sectors and export needs. In addition, it is also necessary to increase profitability, productivity, and output growth in the food and beverage industry sector to increase its competitiveness and a more conducive investment climate because future investment opportunities are still quite large. Keywords: input-output, food and beverage industry